2012
DOI: 10.1007/s10620-012-2036-4
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the Epidermal Growth Factor Receptor Inhibits Epithelial–Mesenchymal Transition in Human Pancreatic Cancer PANC-1 Cells

Abstract: Suppression of EGFR expression can significantly inhibit EMT of pancreatic cancer PANC-1 cells. The mechanism may be related with the down-regulation of the expression of transcription factors snail and slug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 34 publications
0
20
1
2
Order By: Relevance
“…The development of more effective and potent agents for the treatment of cancer is of particular importance considering the widespread problem of resistance to many anti-cancer agents used currently in the clinics, including EGFR inhibitors (28,29,43). In fact, although EGFR inhibitors have shown promise for the treatment of some tumors, their effects are inconsistent and largely affected by the many different mutations and alterations of EGFR encountered in cancer patients (46).…”
Section: Discussionmentioning
confidence: 99%
“…The development of more effective and potent agents for the treatment of cancer is of particular importance considering the widespread problem of resistance to many anti-cancer agents used currently in the clinics, including EGFR inhibitors (28,29,43). In fact, although EGFR inhibitors have shown promise for the treatment of some tumors, their effects are inconsistent and largely affected by the many different mutations and alterations of EGFR encountered in cancer patients (46).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report demonstrated that EGFR RNAi significantly improved cyclopamine sensitivity and decreased AKT and ERK phosphorylation in PC cells [37]. It also decreased migration and invasion capacity of cells, and also decreased the expression of mesenchymal markers such as vimentin and fibronectin, and increased the expression of epithelial marker E-cadherin, suggesting the reversal of EMT by suppression of EGFR expression in PANC-1 cells [38]. To further confirm the inter-relationship between EGFR and miR-146a , we used EGFR siRNA to knock-down EGFR expression and studied the consequence on EGFR expression and cellular behavior.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR signaling has also been linked to EMT [172]. Therapeutic targeting EGFR and its inhibition can cause a reversal of EMT in human pancreatic cancer [172].…”
Section: Role Of Neu1 Sialidase In Cancer Cell Survival and Acquired mentioning
confidence: 99%
“…EGFR signaling has also been linked to EMT [172]. Therapeutic targeting EGFR and its inhibition can cause a reversal of EMT in human pancreatic cancer [172]. Other studies have suggested the potential role of growth factor receptor signaling in establishing chemoresistance of cancer cells [173–176].…”
Section: Role Of Neu1 Sialidase In Cancer Cell Survival and Acquired mentioning
confidence: 99%